2001
DOI: 10.1159/000047622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Secretory Pattern of Plasma Arginine Vasopressin in Stroke Patients

Abstract: Arginine vasopressin (AVP) may play a role in the development of ischemic brain edema and/or cerebral vasospasm. Data available on AVP plasma levels in ischemic stroke are few and discordant. In order to ascertain whether changes in AVP plasma levels occur in ischemic stroke, plasma AVP levels, plasma osmolality and mean arterial pressure were determined in 24 patients with unprecedented ischemic cerebral infarction and in 15 controls over a 24-hour period. In stroke patients, mean 24-hour plasma AVP levels (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 11 publications
1
41
0
Order By: Relevance
“…Traumatic or ischemic brain injury has previously been reported to be accompanied by elevated concentrations of AVP in the plasma (Barreca et al, 2001;Xu et al, 2007). Consistent with these clinical findings, we showed that TBI results in a significant upregulation of hypothalamic synthesis of AVP.…”
Section: Discussionmentioning
confidence: 98%
“…Traumatic or ischemic brain injury has previously been reported to be accompanied by elevated concentrations of AVP in the plasma (Barreca et al, 2001;Xu et al, 2007). Consistent with these clinical findings, we showed that TBI results in a significant upregulation of hypothalamic synthesis of AVP.…”
Section: Discussionmentioning
confidence: 98%
“…In stroke patients, mean 24-h plasma AVP levels are higher than in control subjects and correlate with the severity score of the neurological deficit and the mean size of the lesion (42). In a controlled cortical impact model of brain injury, AVP synthesis was increased in activated microglia and macrophages and in the hypothalamus and cerebral cortex adjacent to the posttraumatic lesion (477).…”
Section: Cerebral Vasospasm and Brain Edemamentioning
confidence: 95%
“…The amount of AVP mRNA and of AVP protein increase after experimental cerebral ischemia (Liu, 1992;Liu et al, 2000) and levels of AVP are elevated in the CSF of stroke patients (Barreca et al, 2001).…”
Section: Avp During Pathologic Conditions Of the Brainmentioning
confidence: 99%
“…Cerebral ischemia induces AVP mRNA (Liu et al, 2000) and protein (Liu, 1992) expression, and increased AVP plasma levels have been reported in stroke patients (Barreca et al, 2001). Application of AVP exacerbates acute ischemic brain edema (Liu et al, 1991;Dickinson and Betz, 1992;Ikeda et al, 1997) and this exacerbation can be reduced by AVP antiserum (Liu et al, 1991) or by the AVP release inhibitor RU51559 (Ikeda et al, 1997).…”
Section: Introductionmentioning
confidence: 99%